IMPLEMENTATED HAY METHOD FOR JOB EVALUATION IN COMPANY AT SIDOARJO - Kelvin Kelvin; Pram Eliyah Yuliana; Sri Rahayu (Research In Management and Accounting (RIMA), 2022)
Job evaluation is very important for the employee being assessed and the company. Job evaluation is a method to determine whether the employee has been in the appropriate position and salary. The Hay method is one method that can be used to evaluate current positions. Hay's method has been standardized and tested in various parts of the world. The Hay method requires information about the job structure, job description, and job specifications, which is then given a point to evaluate the position. The Hay method is applied to a company in the Sidoarjo-East Java, Indonesia, to determine what wages are appropriate for workers with the workload they receive while working in this company. The research was conducted at four levels: manager, head of the department, supervisor, and operator (37 positions). Based on data processing using the Hay method, the position that obtained the highest points was the plant manager position of 752 points with a salary range of Rp. 39,000,000 - Rp. 41,000,000, and the lowest points were cleaning raw material warehouses, machines, and silos with salary ranges. Rp. 3,000,000 – Rp. 5,000,000. The greater the responsibility and workload, the greater the points and salary earned.